2014
DOI: 10.7860/jcdr/2014/9731.4675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between the Analgesic Effect of two Techniques on the Level of Pain Perception During venipuncture in Children up to 7 Years of Age: A Quasi-Experimental Study

Abstract: Background: Distraction techniques are often provided by nurses, parents or child life specialists and help in pain alleviation during procedures. The use of non pharmacological procedures to cope with pain behaviour is less costly and most of these procedures can be administered by a nurse. Hence, the aim of the present study was to assess and compare the analgesic effect of holding the child by a family member versus holding the child by a family member along with an animation distraction intervention on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 8 publications
2
25
0
4
Order By: Relevance
“…, Gupta et al . , Abd El‐Gawad & Elsayed , Karakaya & Gozen , Meiri et al . , Mutlu & Balcı , Moadad et al .…”
Section: Discussionmentioning
confidence: 99%
“…, Gupta et al . , Abd El‐Gawad & Elsayed , Karakaya & Gozen , Meiri et al . , Mutlu & Balcı , Moadad et al .…”
Section: Discussionmentioning
confidence: 99%
“…Children, parents and the nurse observer were blinded to each other's responses. Since the perception of pain varies when parents are present or not, parents were instructed to stay with the children during the procedure (Gupta et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Pharmacological drugs that include tropical anesthetics have often not been very successful as they are costly, may require long periods of time to achieve an analgesic effect (e.g., EMLA®, Ametop ®) or are not found to be effective in all age groups (e.g., vapocoolant sprays) (Cohen et al, 2009;Costello, Ramundo, Christopher, & Powell, 2006;Farion, Splinter, Newhook, Gaboury, & Splinter, 2008). Non-pharmacologic approaches that have been found to be effective in reducing children's acute pediatric pain include but are not limited to, hypnosis, cognitive behavioral therapy, guided imagery, and distraction (Badr, 2013;Gupta et al, 2014;Vetri-Buratti et al, 2015). The use of distracters, such as auditory or visual distracters, bubble blowing, touch, vibration or massage (Bagnasco, Pezzi, Rosa, Fornonil, & Sasso, 2012;Gupta et al, 2014;MacLaren & Cohen, 2005;Sahiner & Bal, 2015), have long been found to be effective in helping the child to cope not only with the immediate medical procedure, but may also buffer memories of the experience (Uman, Chambers, McGrath, & Kisely, 2008).…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…In the literature, the use of comfort strategies has been explored in much more detail for non-ocular procedures. For instance, evidence suggests that the presence of additional people, whether they are family members or additional staff, may divert attention away from pain during procedures such as venipuncture in children [14]. Handholding has likewise been shown to be a very effective coping strategy in pain perception during procedures such as blood draws, shunt placements, and peripheral chemotherapy [15].…”
Section: Introductionmentioning
confidence: 99%